Critical Factors and Mitigating Measures of Construction Delays of Pakistani Building Construction Projects - Irfanullah; Hasmori, Muhammad Fikri; Memon, Mujtaba Hassan; Ismail, Radzi (International Journal of Sustainable Construction Engineering and Technology, 2023)
The construction industry is a significant contributor to a country's Gross Domestic Product (GDP). However, construction projects often face many issues especially delay. It is a key contributor to project failure, leading to cost overruns and a decline in quality standards. This study aims to identify the critical factors of delay in building construction projects in Pakistan, and its controlling measures of the critical delay factors. A literature review identified 48 common factors of delay in the construction industry worldwide. Based on a structured questionnaire and the average index method, 11 critical factors of delays in building construction projects in Pakistan were identified. Furthermore, a semi-structured questionnaire was used to determine 44 possible mitigation measures which were extracted from literature review with the 11 critical delay factors.  The results of this study will be useful for stakeholders in building construction projects in Pakistan. By incorporating the recommended mitigation measures, they can identify and control the most critical factors that can cause delays in building construction projects. This study contributes to the existing literature by providing a better understanding of the factors causing delays in building construction projects in Pakistan and proposing effective measures to mitigate these factors.